Effects of Curing Conditions and Combined Pozzolanic Material on Compressive Strength of Reactive Powder Concrete - Said Jalalul Akbar; Yulius Rief Alkhaly; Maizuar Maizuar; M Ibnu H F Harahap (Malikussaleh University, Aceh, Indonesia, 2025)
Reactive Powder Concrete (RPC) is a type of concrete with an extremely dense matrix and high compressive strength. The compressive strength of RPC was examined in this study to evaluate the effects of the combination of silica fume (SF) and rice husk ash (RHA) with up to 50% by weight of cement, which provided the highest compressive strength and low cement content under normal curing and steam curing methods. The results showed that the combination of 5% SF or 10% SF with 25% - 45% RHA reaches compressive strength over 100 MPa at the age of 28 days with a low cement content of about 650 kg/m3 under both curing conditions and maintains the slump flow more than 200 mm. This study demonstrates that SF and RHA can be used up to 50% by weight of cement to produce RPC with a compressive strength of over 100 MPa.